Evaluation of a Question Prompt List About Cardiovascular Disease Risk and Prevention After Hypertensive Pregnancy: A Pilot Study - Smita Dhakal; Bethany Rankin; Taryn Assaf; Jane Baker; Laura Chisick; Tracey Colella; Natalie Dayan; Maureen Dobbins; Sherry Grace; Serena Gundy; Sheila O'Keefe McCarthy; Ziran Meng; et al. (Health Expectations)
ABSTRACT Introduction The aim of this study was to pilot test a question prompt list (QPL) about cardiovascular disease (CVD) risk reduction after hypertensive pregnancy (HDP). Methods In a prospective cohort study of adult women who had HDP given the QPL before and surveyed after a physician visit, we assessed perceived person‐centred care, self‐efficacy for self‐management, perceived self‐management and QPL feasibility. Results Twenty‐three women participated: 57% of diverse ethno‐cultural groups, 65% < 40 years of age and 48% immigrants. Most scored high for person‐centred care (mean 4.1 ± 0.2/5); and moderately for self‐efficacy (mean 7.4 ± 0.6/10) and self‐management (mean 3.1 ± 0.3/5). Most appreciated QPL design and reported QPL benefits: helped them to prepare for the visit and know what to ask; increased confidence to ask questions, knowledge of the link between HDP and CVD and lifestyle behaviours to reduce CVD risk. Most reported that physicians were receptive to discussing QPL questions. Conclusion Women appreciated the QPL and knowledge about self‐management was high but self‐efficacy for or perceived self‐management was moderate. It appears feasible to share a QPL with ethno‐culturally diverse women who can share it with physicians to facilitate discussions about post‐pregnancy HDP‐related CVD risk. Patient or Public Contribution This study involved women who experienced HDP and engaged ethno‐culturally diverse women with lived experience of HDP as study advisors in all stages of the research.